Kulturasetro i Danmark? : En indledende undersøgelse - Schjødt, Uffe (Religionsvidenskabeligt tidsskrift, 2022)
ABSTRACT: Inspired by the concept of Cultural Christianity, we investigate if something like Cultural Asatru exists in Denmark. A Cultural Asatru person may not believe in or worship the Old Norse gods, but may still identify with a pre-Christian heritage, believe that Danish values stem from Old Norse culture, and see Old Norse myths as original expressions of these values. We have used qualitative and quantitative methods to examine such beliefs and attitudes in 30 participants. The study was designed as a proof-of-concept study to evaluate whether cultural Asatru exists in Denmark, and if so, how this construct can be measured empirically. We find that national conservative Danes identify with Christian as well as Old Norse culture. The virtues of strength, courage, and vigor seem to be strongly associated with Old Norse heritage, while forgiveness, love, and compassion are associated with a Christian heritage. Gender equality, appreciation of nature, and the concept of Danishness appear to be associated more with Old Norse culture than with Christian culture. Strength and courage, which seem to express the essence of Old Norse culture, are heavily associated with the god Thor and the widespread wearing of Thor’s hammer pendants.